Peran Guru dan Pemahaman Psikologi Anak dalam Pembelajaran - Astuti, Mardiah; Mutyati, Mutyati; Ibrahim, Ibrahim; Rika, Rika; Lia, Sesi; Kharisma, Windi; Triwahyuni, Diana (Universitas Pendidikan Mandalika, 2024)
Abstract: This research aims to analyze the role of teachers and child psychology in the learning process of third-grade students at State Elementary School 157 Palembang. The method used in this research is qualitative. By using a qualitative descriptive approach, this research is expected to comprehensively describe the roles of teachers and child psychology in learning. Data collection techniques used include interviews, observations, and documentation. The results of this research discuss the roles of teachers and child psychology in the learning process of third-grade students at State Elementary School 157 Palembang. The roles of teachers and understanding child psychology include understanding the characteristics of each student, adopting an approach, and also understanding the conditions that children have in participating in learning activities. Educators are sensitive to the conditions of each of their students and then approach slowly by asking about the difficulties they are facing. In addition to teachers playing a role in the development of child psychology, parents also play a very important role in the development of child psychology, especially at home. The relationship between teachers and parents must be continuous, with good communication and cooperation, to achieve the best goals for the development of child psychology. Keywords: Teacher Role, Understanding Child PsychologyAbstrak: Penelitian ini bertujuan untuk menganalisis peran guru dan psikologi anak dalam proses pembelajaran siswa kelas III SD Negeri 157 Palembang. Metode yang digunakan dalam penelitian ini adalah kualitatif. Dengan menggunakan pendekatan deskriptif kualitatif, penelitian ini diharapkan dapat mendeskripsikan secara komprehensif tentang peran guru dan psikologi anak dalam pembelajaran. Teknik pengumpulan data yang digunakan, yaitu wawancara, observasi dan dokumentasi. Hasil penelitian ini adalah membahas tentang peran guru dan psikologi anak dalam pembelajaran siswa kelas III SD Negeri 157 Palembang. Adapun peran guru dan pemahaman psikologi anak diantaranya memahami karakter dari setiap peserta didik, mengadakan sebuah pendekatan dan juga harus memahami dari setiap kondisi yang dimiliki anak-anak dalam mengikuti kegiatan pembelajaran. Tenaga pendidik peka terhadap kondisi dari setiap peserta didiknya dan kemudian melakukan pendekatan secara perlahan dengan cara bertanya mengenai kesulitan apa yang sedang ia hadapi. Selain guru yang berperan dalam perkembangan psikologi anak, orang tua juga berperan sangat penting dalam perkembangan psikologi anak terutama di rumah. Hubungan guru dan wali murid haruslah berkesinambungan satu sama lain, dengan adanya komunikasi yang berjalan baik serta kerjasama yang baik, maka dapat mencapai tujuan yang baik bagi perkembangan psikologi anak tersebut.Kata Kunci:Â Peran Guru, Pemahaman Psikologi Anak